Peran Kitab Ta'limul Muta'allim Dalam Pembentukan Karakter Islami Pada Santri Di Pondok Pesantren Sabilul Hasanah - Lusi Isnawati; Nuraida .; Silvia Assoburu (CV. ITTC INDONESIA, 2026)
This study aims to determine the role of the Ta’limul Muta’allim book in shaping the Islamic character of students at Sabilul Hasanah Islamic Boarding School. The Ta’limul Muta’allim book is a classical Islamic text that contains ethical guidelines in seeking knowledge, which are highly relevant in forming students' personalities. This research uses a qualitative approach with a descriptive research type. Data collection techniques include observation, interviews, and documentation involving caregivers, teachers, and students at the Islamic boarding school. The results show that the Ta’limul Muta’allim book plays a significant role in shaping students' Islamic character, such as humility (tawadhu), discipline, respect for teachers, sincerity in seeking knowledge, and responsibility in daily life. The implementation of this book is carried out through regular learning sessions, role modeling by teachers, and daily habituation within the boarding school environment. In addition, the values contained in the book strengthen the spiritual and moral aspects of students, forming individuals with noble character.